Treatment of A Class II Malocclusion Case having Low Mandibular Angle & Deep Bite with Inter-arch Elastics and Reverse Curve Archwire - Mustafa, MT (Bangladesh Journal of Dental Research & Education, 2013)
Inter-arch elastics and reverse curve arch wire can be used successfully in the treatment of deep bite malocclusions and are two of the most common methods available for treating class II malocclusions . Careful diagnosis and treatment planning is primordial for choosing the right treatment modality which can vary from patient to patient. The subject treated in this study was a 14 years old female patient with a Class II division 2 Angles malocclusion having a skeletal deep bite of around 6 mm and an overjet of 1.5mm, deep curve of spee, coinciding upper and lower arch midlines with that of the facial midline. After analysis made, the case was treated without any extraction due to the fact that she was a low mandibular angle patient with minimal amount of crowding in both the arches and also a Combination Factor of 171.5° (greater than 155.9°) which represents the balance of both the vertical and horizontal dimensions. The Anterior Posterior Dysplasia Indicator value fell within the normal range indicating a Class I horizontal maxillo-mandibular relationship. The duration of the treatment was around 20 months. After achieving the goals of the treatment, cephalogram was taken and the pre and post treatment variables compared. The correction of the deep overbite condition was achieved successfully along with the correction of the molar relationship into a Class I malocclusion. U1-SN has increased by 50.0 and L1-NA increased by 4.50 together with a decrease in the inter-incisal angle by 8.50 contributing to a decrease in bite depth. The assessment of the cephalometric findings showed that the lower anterior facial height change was minimal but not insignificant partly due to the continued growth of the mandible which can be confirmed through the values of FMA which shows an increase in 20.0, Facial Height Index dropping from 0.89 to 0.88 and the TPFH:TAFH values decreasing by 0.8%. But this change was not enough to have a positive impact on the facial appearance of the subject. Change in the molar relationship was aided by the use of inter-arch elastics and the deep bite correction facilitated by the slight rotation of the occlusal plane caused by extrusion of lower first molar along with the flaring of the lower incisors induced through the use of the reverse curve arch wire. So it was confirmed that the combined use of inter arch elastics & reverse curve arch wire help to correct the class II division 2 malocclusion along with some improvement for increasing the lower anterior facial height.